Proximate Analysis Of Collagen Cockatoa Fish Scales (Scarus sp.) - Herson, Nur Afiah; Sumual, Maria Fransisca; Rumengan, Inneke F. M; Pongoh, Jantje; Mandey, Lucia C. (Sam Ratulangi University, 2023)
Collagen is the main component of the dermis layer of skin (bottom of the epidermis) which is made by fibroblast cells. Collagen sourced from marine biological materials in the form of properly extracted fish scales can be an alternative source to collagen from cows and pigs. This research aims to analyze the composition of the collagen material (proximate) of Cockatua fish (Scarus sp) scales. This research was carried out in March 2023 – August 2023 at the regional technical implementation unit, Laboratory for Development and Quality Testing of Fishery Products, Gorontalo Province. Proximate analysis of parrot fish scale collagen was carried out on four parameters, namely water content, ash content, fat content and protein content. The proximate analysis method refers to the SNI 2354.2:2015 (moisture content), SNI 01-2354.1-2006 (dust content), SNI 01-2354.4-2006 (protein content), SNI 2354-3:2017 (fat content). The water content of parrotfish scale collagen is 4.35%, ash content is 0.76%, protein content is 82.17% and fat content is 1.18%. From the results of the proximate analysis it is known that all observation parameters have met BSN 8076:2014 standards. Keywords : Collagen, parrot fish scale, proximate Abstrak Kolagen merupakan komponen utama lapisan kulit dermis (bagian bawah epidermis) yang dibuat oleh sel fibroblast. Kolagen yang bersumber dari bahan hayati laut berupa sisik ikan yang terekstraksi dengan tepat dapat menjadi sumber alternatif selain kolagen dari sapi dan babi. Penelitian ini bertujuan untuk menganalisis komposis bahan (proksimat) kolagen sisik ikan kakatua (Scarus sp). Penelitian ini dilaksanakan pada bulan Maret 2023 – Agustus 2023 di unit pelaksana teknis daerah Laboratorium Pembinaan dan Pengujian Mutu Hasil Perikanan Provinsi Gorontalo. Analisis proksimat kolagen sisik ikan kakatua dilakukan pada empat parameter yaitu kadar air, kadar abu, kadar lemak dan kadar protein. Metode analisis proksimat mengacu pada metode SNI 2354.2:2015 (kadar air), SNI 01-2354.1-2006 (kadar debu), SNI 01-2354.4-2006 (kadar protein, SNI 2354-3:2017 (kadar lemak). Hasil penelitian menunjukkan kadar air dari kolagen sisik ikan kakatua yaitu 4.35 %, kadar abu 0.76 %, kadar protein 82.17 % dan kadar lemak 1.18 %. Dari hasil analisis proksimat diketahui seluruh parameter pengamatan telah memenuhi standar BSN 8076:2014. Kata kunci : kolagen, sisik ikan kakatua, proksimat.